Penegakan Hukum Kantor Imigrasi Kelas II TPI Belawan Terhadap Warga Negara Asing Yang Menyalahgunakan Izin Tinggal - Leonyta Rotua; M. Citra Ramadhan; Rizkan Zulyadi (Mahesa Research Center, 2023)
The purpose of this study is to analyze the law enforcement process, obstacles in supervision and law enforcement against criminal acts of violation of residence permits for foreign nationals in Class II TPI Belawan Immigration Offices. The research method used is an empirical legal research method. Empirical legal research is carried out by collecting primary data as the first source by going through empirical results obtained through interviews with the Head of Class II Immigration Office TPI Belawan. This research is a descriptive analysis which is analyzed qualitatively. Based on the results of this study, enforcement of foreign nationals who abuse their residence permits in the Belawan area in 2022 will be subject to Immigration Administration Actions in the form of prevention and deterrence, detention, delegation of detention centers and deportations. In the process of detaining foreign nationals prior to deportation, rights are given according to their basic daily needs. Obstacles in general are unresponsive coordination with embassies, minimal human resources for both immigration officials and PPNS in terms of supervision and law enforcement and relatively long time in completing case files. In particular, there are frequent tidal floods, unstable electrical voltage, and buildings that can be said to be unfit. Supporting factors are the presence of TIMPORA (Foreigner Monitoring Team); There is APOA (Alien Reporting Application).